Cytoreductive surgery plus hyperthermic intraperitoneal chemotherapy with oxaliplatin for peritoneal carcinomatosis arising from colorectal cancer. Issue 7 (9th September 2013) - Gervais, Mai‐Kim; Dubé, Pierre; McConnell, Yarrow; Drolet, Pierre; Mitchell, Andrew; Sideris, Lucas
Abstract Background Peritoneal carcinomatosis (PC) from colorectal cancer is associated with a poor prognosis. Cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) have improved survival compared to systemic chemotherapy. We evaluate the results of this treatment in our institution. Methods Treatment consisted of complete CRS followed by HIPEC with oxaliplatin (460 mg/m2) in 2 L/m2 of D5W at 42°C during 30 min. Results From 2004 to 2011, 40 patients with PC from colorectal cancer were included and 25 CRS + HIPEC were performed. Six patients had a negative second‐look surgery and nine had unresectable disease. Median follow‐up was 22.8 months. Overall 3‐ and 5‐year survival rates for the cohort were 56% and 33%. The 3‐ and 5‐year overall survival rates were 61% and 36% for HIPEC group, 82% and 67% for patients with negative second‐look, and 22% and 0% for the unresectable group (P = 0.0087). 3‐year disease‐free survival for HIPEC group was 22%. Major complication and mortality rate for HIPEC group were 20% and 4%. Peritoneal carcinomatosis index (P = 0.0374) and lymph node status (P = 0.027) were prognostic indicators. Conclusions CRS + HIPEC with oxaliplatin for PC from colorectal cancer is an effective treatment with encouraging survival results. J. Surg. Oncol. 2013; 108:438–443. © 2013 Wiley Periodicals, Inc.